Bibliometric Mapping of Gamification in Education - Dikmen, Melih; Bahadır, Ferdi (Murat TUNCER, 2022)
This study aims to reveal the research trend in the field of gamification in education with co-authorship, bibliographic matching, collaboration and citation analysis, taking into account variables such as author, publication, keyword, journal, country, university, number of publications and citations. VOSviewer software was used for bibliometric analysis. As a result of the bibliometric analysis, it has been determined that the most effective countries in terms of studies on gamification in education are the USA, Spain and Bulgaria. According to the keyword co-occurrence analysis, it was determined that keywords such as gamification, motivation, game elements and educational innovation came to the fore. The use of gamification in education has some important effects such as motivation, learning success, interaction, competition and innovation. Current research provides the most relevant theoretical contributions from an innovative technique in the field of bibliometric research. In addition, it can be said that the results of the study are not only aimed at the academic community, but also addressed to educators and politicians in order to identify trends in research on gamification in education, design effective policy tools and ultimately improve education and training environments. The results show that research on gamification in education is focused on current developments.

Bu çalışma, yazar, yayın, anahtar kelime, dergi, ülke, üniversite, yayın ve atıf sayısı gibi değişkenler dikkate alınarak ortak yazarlık, bibliyografik eşleşme, birlikte çalışma ve atıf analizleri ile eğitimde oyunlaştırma alanındaki araştırma eğilimini ortaya koymayı amaçlamaktadır. Bibliyometrik analiz için VOSviewer yazılımı kullanılmıştır. Bibliyometrik analiz sonucunda eğitimde oyunlaştırma alanına ilişkin yapılan çalışmalar açısından en etkili ülkelerin ABD, İspanya ve Bulgaristan olduğu belirlenmiştir. Anahtar kelime eş oluşum analizine göre gamification, motivation, game elements ve educational innovation gibi anahtar kelimelerin öne çıktığı belirlenmiştir. Eğitimde oyunlaştırmanın kullanılması motivasyon, öğrenme başarısı, etkileşim, rekabet ve inovasyon gibi bazı önemli etkileridir. Mevcut araştırma, bibliyometrik araştırmalar alanında yenilikçi bir teknikten en alakalı teorik katkıları sağlar. Ek olarak çalışmanın sonuçları yalnızca akademik topluluğa yönelik olmayıp, aynı zamanda eğitimde oyunlaştırma konulu araştırmaların eğilimlerinin belirlenmesi, etkili politika araçları tasarlanması ve nihayetinde eğitim ve öğretim ortamlarının iyileştirilmesi amacıyla eğitimcilere ve politikacılara da hitap ettiği söylenebilir. Sonuç olarak eğitimde oyunlaştırma ilgili araştırmalarının güncel gelişmeler odağında ele alındığını göstermektedir.
Eğitimde Oyunlaştırmanın Bibliyometrik Haritalandırılması
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar